BUDGET PREPARATION, REPORTING AND MEASUREMENT, AND FINANCIAL PERFORMANCE: A STUDY ON ADVENTIST HIGHER EDUCATION IN SOUTH-EAST ASIAN REGION - Siagian, Harlyn Lindon (Jurnal Ekonomis, 2015)
Each organization expect a satisfactory performance, specially in financial performance. Management organization was expetec to achieve the goal of organization. In this study, the performanceis measured by financial as dependent variable, budget preparation, and repoting and measurement aas independent variables. The respondent of this research was reguler worker of Adventist higher education in South East Asian region (SSD). The instrument of this study was questionnaire and measured by perceptions of respondent. Independent variable (budget preparation, and reporting measurement) had very strong positive (0.610) to financial performance. Constant value was 28.957, the amount offinancial performance primarly irifluence by greater budget preparation (0.153) andfollowed by reporting and measurement (0.403). Keywords: budget, measurement, financial performance